"In the Listening World": The Poetry of Duncan Campbell Scott - Kelly, Catherine (Studies in Canadian Literature, 1979)
Consciousness of a large, essential life force at the core of one’s being seems basic to Duncan Campbell Scott’s poetry. Appearing virtually in every context of his writing as its inspiration, such an experiential awareness of fundamental life reveals itself as being compelling and fulfilling, personal and intimate, unsettling and mysterious. Investigating the compelling and fulfilling quality of this transcendent encounter as it is perceived by the listener leads to the probable source of the sense of vagueness which seems to adhere to Scott’s poetry.